Efficacy and safety of transfemoral TAVR in pure aortic regurgitation patients: a single center study - Jie Feng; Haixia Wei; Shiyuan Zhang; Yao Li; Hangyu Liu; Yanqing Wu (Scientific Reports)
Abstract The objective of this study was to evaluate the efficacy of transcatheter aortic valve replacement (TAVR) via the femoral approach in patients with pure aortic regurgitation (AR), with a focus on mortality, adverse event rates, cardiac function, and clinical symptom improvement. The study utilised a single-centre experience to provide insights and offer guidance for the management of TAVR in AR patients. Patients with aortic valve pathology who underwent TAVR at the Second Affiliated Hospital of Nanchang University, from January 2018 to March 2023 were enrolled. They were classified into two groups: pure AR and aortic stenosis (AS) based on preoperative transthoracic echocardiography. We compared baseline characteristics, imaging data, surgical outcomes, and follow-up conditions between them. We focused on the safety and efficacy of TAVR in patients with AR and evaluated these results using regression analysis. The study cohort comprised 87 patients, with 21 in the AR group and 63 in the AS group. We revealed that AR patients exhibited low mortality and adverse event rates following transfemoral TAVR, with notable improvements in postoperative cardiac function and substantial symptom relief. However, the rates of paravalvular leak (PVL), permanent pacemaker (PPM) implantation, and valve-in-valve procedures were relatively elevated. While these findings suggest that TAVR may represent a viable therapeutic option for patients with AR, the elevated rates of PVL, PPM implantation, and readmission underscore the need for further investigation, with larger cohorts and extended follow-up, to more robustly evaluate the long-term safety and efficacy of this approach.